Calf Circumference at birth- A Procedure To Screen Low Birth Weight Babies - POTDAR, D. B.; NALLA, VEDA VYAS (International Journal of Psychosocial Rehabilitation, 2020)
In spite of intercessions being taken, low birth weight despite everything endures as a general medical issue in low and center salary nations. World Health Organization characterizes low birth weight as birth weight under 2500 gm. There is a consistent inquiry to discover more current techniques to identify low birth weight babies with the goal that early strategies can be founded. This investigation was directed to assess calf outline as method to screen low birth weight babies in tertiary consideration medical clinic in KIMS karad.. A cross sectional study was conducted in tertiary care hospital of KIMS karad, Maharashtra for a period of 4 months. The study subjects were babies delivered at the hospital. Birth weight was recorded utilizing an advanced gauging scale inside 24 hours of the conveyance. Length, calf perimeter, head and chest periphery were estimated by standard rules. Results: Larger part of moms were in the age gathering of 20 to 24 years old gathering, were taught up to elementary school and had a place with Hindu religion. The mean calf outline of low birth weight babies was 9.64±1.13 cm and was 10.96±1.01 cm in ordinary weight babies. The mean estimations of calf periphery were fundamentally lower in low birth weight babies (p <0.001). The affectability and explicitness for the best cut off of calf outline was seen as 89.97% and 42.86%respectively. Conclusions: Estimating calf boundary was seen as a decent test with higher affectability yet lower particularity. Henceforth, calf perimeter can be utilized as an elective strategy to screen babies conceived in remote regions, where the office of gauging the child during childbirth isn’t accessible.